PENGARUH REKRUTMEN, PENEMPATAN KERJA DAN KOMPENSASI FINANSIAL TERHADAP PRODUKTIVITAS KARYAWAN PT. ADIRA FINANCE CILEDUG KOTA TANGERANG - Andriani, Desika; Prasetiyo, Muhammad Imam (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to determine the effect of Recruitment, Job Placement, and Financial Compensation on Employee Productivity at PT. Adira Finance Ciledug, Tangerang City, both partially and simultaneously. Data collection was conducted using a convenience sampling method, with a total population of 79 respondents at PT. Adira Finance Ciledug, Tangerang City. The data used in this study include a validity test of the variables Recruitment, Job Placement, and Financial Compensation on Employee Productivity, where the calculated r value is greater than the table r value of 0.2213. The results of the reliability test using the Cronbach Alpha formula show that the r value is > 0.6, namely r alpha for Recruitment (0.873), Job Placement (0.806), Financial Compensation (0.808), and Employee Productivity (0.818). The classical assumption test is used to strengthen the multiple linear regression analysis by using 3 classical assumption tests, namely the normality test, the multicollinearity test, and the heteroscedasticity test, where the 3 tests are free from the classical assumption test (the test is suitable for use). The results of the multiple linear regression analysis in this study are Y = 0.870 + 0.328 (X1) + 0.261 (X2) + 0.394 (X3) while the coefficient of determination (R2) is 0.674 or 67.4%, which means that Recruitment, Job Placement, Financial Compensation on Employee Productivity explains the variation in Employee Productivity by 67.4%. The t-test and F-test showed a significant effect both partially and simultaneously. The t-test results for Recruitment were greater than the t-table (3.823>1.99210), for Job Placement were greater than the t-table (2.381>1.99210), and for Financial Compensation were greater than the t table (3.231>1.99210). The F-test showed a calculated F-value of 54.640>F-table 2.73 with a significance level of 0.000 <0.05. Therefore, Ho was rejected and Ha was accepted. Therefore, it can be concluded that the variables of Recruitment, Job Placement, and Financial Compensation at PT. Adira Finance Ciledug, Tangerang City have a positive and significant effect on Employee Productivity both partially and simultaneously.